Kerjasama UNODC dengan Pemerintah Indonesia dalam Pelaksanaan Country Programme - Sekunda, Savero Naufal; Windiani, Reni (Journal of International Relations, 2018)
The purpose of this study is to illustrate the cooperation between the UNODC and thegovernment of Indonesia in tackling drug cases in Indonesia, related to the CountryProgram of the period 2012-2015. The research method used in this research is qualitativemethod, analytical descriptive research type, and through literature study techniques andinterviews. The cooperation in this study was analyzed using the Institutional Liberalismperspective, related to the cooperation of the country with international institutions. Theresults of this analysis have proven that the cooperation between Indonesia and theUNODC in the 2012-2015 Country Program has been successful because it can give rise toharbor security through capacity improvements and technical assistance as well asproviding information obtained through World Customs Organization (WCO) andCountainer Control Program (CCP) to the government of Indonesia, the UNODC alsoprovides Computer Based Training (CBT) for law enforcement in Indonesia and providesequipment that can improve law enforcement ability in Indonesia related to drugsmuggling at the borders or harbors.